FACTOR DETERMINATION OF THE RELATIONSHIP OF PUBLIC CONFIDENCE IN THE IMPLEMENTATION OF PROGRAMS IN THE FIELD OF PHYSICAL CULTURE AND SPORTS AT THE PLACE OF RESIDENCE - M. Yu. Burtsov (Вестник университета, 2019)
The content of the phenomenon of trust as a mechanism for strengthening social stability and ensuring the harmonious interaction of government and society has been revealed on the example of the development of programs for the development of physical culture and sports at the place of residence. The author’s understanding of the factor determination of trust relations has been presented. On the basis of the analysis of implemented programs, plans and activities in the field of physical culture and sports the specificity of legal, socio-economic and socio-cultural factors of confidence building has been shown. According to the results of expert research, the proposals to improve the management of relations of trust in the system of sports institutions, in particular in the system of training of the Olympic reserve (on the example of the Moscow region), have been substantiated.